USM SCHOOL OF CHEMICAL SCIENCES HELPS NURTURE YOUNGER GENERATIONS TO BASIC SCIENCE EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 10 October 2016 Science is a core subject in the school curriculum from primary to secondary schools where students are provided basic scientific knowledge and science literacy skills in order to continue their science education at the upper secondary level, taught to apply scientific knowledge in decision making and problem solving in daily life and elective science subjects prepare them for the study of science at the postsecondary level.